Maternal risk factors involved in specific congenital anomalies of the kidney and urinary tract: A case–control study. Issue 7 (4th April 2016) - Groen in 't Woud, Sander; Renkema, Kirsten Y.; Schreuder, Michiel F.; Wijers, Charlotte H.W.; van der Zanden, Loes F.M.; Knoers, Nine V.A.M.; Feitz, Wout F.J.; Bongers, Ernie M.H.F.; Roeleveld, Nel; van Rooij, Iris A.L.M.
Abstract : BACKGROUND: Congenital anomalies of the kidney and urinary tract (CAKUT) comprise a heterogeneous group of birth defects with a variety of genetic and nongenetic factors suspected of involvement in the etiology. However, little is known about risk factors in specific CAKUT phenotypes. Therefore, we studied potential maternal risk factors in individual phenotypes within the CAKUT spectrum. METHODS: Questionnaire data were collected from parents of 562 children with CAKUT and 2139 healthy controls within the AGORA data‐ and biobank. Potential maternal risk factors investigated included folic acid use, overweight and obesity, smoking, alcohol consumption, subfertility, and diabetes mellitus. We performed logistic regression analyses to assess associations between these potential risk factors and CAKUT phenotypes. RESULTS: Increased risks of CAKUT were observed for folic acid use and maternal obesity, while fertility treatment by in vitro fertilization or intrauterine insemination and diabetes diagnosed during pregnancy also seem to be associated with CAKUT. Use of multivitamins reduced the risk (odds ratio [OR], 0.5; 95% confidence interval [CI], 0.2–1.0) as opposed to use of folic acid supplements only (OR, 1.3; 95% CI, 1.0–1.8). Folic acid use was associated with duplex collecting systems (OR, 1.8; 95% CI, 1.0–3.4) and vesicoureteral reflux (OR, 1.8; 95% CI, 1.1–2.9) in particular. A relatively strong association was observed between diabetes during pregnancy and posterior urethral valves (OR, 2.6; 95% CI, 1.1–5.9). CONCLUSION: Use of folic acid only seems to be counterproductive for prevention of CAKUT, in contrast to multivitamin use. Furthermore, we observed differences in risk factor patterns among CAKUT phenotypes, which stress the importance of separate analyses for each phenotype. Birth Defects Research (Part A) 106:596–603, 2016. © 2016 Wiley Periodicals, Inc.